Broadband: A Solution for Rural e-Learning? - Robin Mason (Athabasca University Press, 2004)
Rural and remote learners are disadvantaged even with online provision due to poor connections. Broadband offers a potential solution. This paper looks at the initial results of a project to install broadband services in the Western Isles of Scotland. It focuses on the educational potential of broadband and the design implications for online courses. It also considers more informal kinds of learning that broadband facilitates in rural areas.